Olfactory marker protein interacts with adenosine nucleotide derivatives - Noriyuki Nakashima (Biochemistry and Biophysics Reports, 2021)
Olfactory marker protein (OMP) is a genetic signature for mature olfactory receptor neurons (ORNs). Recently, it has been proposed that OMP directly captures odour-induced cAMP to swiftly terminate the olfactory signal transduction to maintain neuronal sensitivity. In the present study, we show that OMP can also interact with other adenosine nucleotides as ATP, ADP and AMP with different affinities. We performed bioluminescent resonant energy transfer (BRET) assay to measure the binding actions of the adenosine nucleotide derivatives in competition to cAMP. Amongst all, ATP showed the bell-shape affinity to OMP in the presence of cAMP; ADP and AMP showed fewer affinities to OMP than ATP. In the absence of cAMP analogues, ATP alone bound to OMP in a dose dependent manner with a lower affinity than to cAMP. Thus, OMP possessed different affinities to ATP in the presence or absence of cAMP. OMP may interact differentially with ATP and cAMP depending on its supply and demand along the cAMP-associated signalling in the limited spaces of cilia of ORNs.